Tree Diversity Enhance Species Richness of Beneficial Insect in Experimental Biodiversity Enrichment in Oil Palm Plantation - Azru Azhar; Muhammad Iqbal Tawakkal; Adha Sari; Akhmad Rizali; Suria Darma Tarigan; Rizky Nazarreta; Damayanti Buchori (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2022)
Integrating plantation landscape with vegetation/tree diversity has been proposed as a strategy to maintain crop production (for livelihood) while increasing biodiversity, habitat complexity and ecological functions. The objective of this research was to investigate the influence of tree biodiversity in experimental biodiversity enrichment in oil palm plantation to beneficial insects, especially ants and parasitoid wasps in the EFForTS-BEE research plot. Beneficial insects in experimental enrichment oil palm plantation are very important to be studied so that ecosystem services that are related with the changes of the plant structures over time can be understood better. Insect collections were done in two years, 2018 and 2019. Direct sampling was used to collect actual insects, pitfall traps to trap ground dwelling insects, yellow pan traps and malaise trap to trap low-flying insects, and sweep net to collect general insects. Overall, we collected 76 species of 6423 individual ants, and 174 morphospecies of 867 parasitoid wasps in this research. Abundance of ants and parasitoid wasps were not influenced either by tree diversity level in the plot nor the various plant diversity. In contrast, tree diversity level has strongly influenced species richness of ants and partially affected species richness of parasitoid wasps. In conclusion, there are positive correlation between ants’ and parasitoid wasps’ species richness and vegetation abundance.